2021
DOI: 10.1155/2021/7734162
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Production-Education Integration Performance of the High-Tech Industry: An Empirical Comparison between Three Urban Agglomerations in China

Abstract: Deepening production-education integration (PEI) is a major strategy of China to reinforce education reform and promote industry transformation. Different from the traditional research perspective of colleges on the supple side, this paper chooses to evaluate the PEI performance of the high-tech industry from the angle of industry on the demand side. Firstly, the action mechanisms of the education system and industry system in PEI were expounded, and the design framework of the evaluation index system (EIS) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…However, from the four latitudes of "internal evolution of spirals, mutual influence among spirals, coverage of new trilateral network, organization generated from the interaction of three spirals, and regression effect of triple spiral network", which constitute the triple spiral model theory, the three are not going their own way, nor are they simply pairwise relations, but one of them. In the regional innovation system, the internal functions of the three are constantly evolving, and they are intertwined and interact with each other, forming a continuous and close strategic partnership, jointly promoting the production, transformation, application and upgrading of knowledge, jointly realizing the effective connection between professional chain and industrial chain, and jointly promoting the coordinated development of regional education, economy and society [10][11].…”
Section: Integration Of Production and Education Benefits And Demand ...mentioning
confidence: 99%
“…However, from the four latitudes of "internal evolution of spirals, mutual influence among spirals, coverage of new trilateral network, organization generated from the interaction of three spirals, and regression effect of triple spiral network", which constitute the triple spiral model theory, the three are not going their own way, nor are they simply pairwise relations, but one of them. In the regional innovation system, the internal functions of the three are constantly evolving, and they are intertwined and interact with each other, forming a continuous and close strategic partnership, jointly promoting the production, transformation, application and upgrading of knowledge, jointly realizing the effective connection between professional chain and industrial chain, and jointly promoting the coordinated development of regional education, economy and society [10][11].…”
Section: Integration Of Production and Education Benefits And Demand ...mentioning
confidence: 99%
“…As a largely agricultural country, China has long been lacking rural talent as an important bottleneck factor affecting and restricting agricultural and rural development, and the lack of talent is the main aspect of the contradiction from the perspective of the two-point theory and focus theory. We should strengthen rural construction and accelerate the cultivation of rural talents to serve rural revitalization [7][8]. The revitalization of rural talents plays a key role in the process of rural revitalization, and the implementation of rural revitalization requires a "three rural" workforce that understands agriculture and loves rural areas and farmers [9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang, Q et al evaluated the integration of industry and education in three economic development zones through the correlation entropy complex meta (CECME) model and the coupling degree of coordination (CCD) model, and they found that the degree of integration of industry and education is positively correlated with the high-quality development of the regional economy. Therefore, the integration of industry and education can be a major strategy to strengthen education reform and promote industrial transformation in China [11].…”
Section: Introductionmentioning
confidence: 99%